2013
DOI: 10.36076/ppj.2013/16/479
|View full text |Cite
|
Sign up to set email alerts
|

Indications for Repeat Diagnostic Medial Branch Nerve Blocks Following a Failed First Medial Branch Nerve Block

Abstract: No studies have directly measured the false negative rate of medial branch block (MBB) with correlation to medial branch neurotomy (MBN) outcome. We investigated the potential false negative MBB rate and the subsequent MBN outcome on a consecutive audit of all patients undergoing a double MBB protocol. We prospectively collected audit data and retrospectively collected data by phone on 229 consecutive patients undergoing diagnostic MBB. One-hundred-twenty-two patients reporting greater than 50% of subjective p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
6
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 23 publications
4
6
1
Order By: Relevance
“… 8 , 38 , 39 , 42 The false-negative rate may be magnified by imaging modalities that miss the target nerve or cannot reliably detect intravascular uptake. 11 The findings of this meta-analysis suggest that US-guided MBB could further impede the ability to accurately identify patients for radiofrequency denervation. However, use of US may be indicated in austere environments or select clinical scenarios where avoiding radiation exposure is a key outcome.…”
Section: Discussionmentioning
confidence: 94%
“… 8 , 38 , 39 , 42 The false-negative rate may be magnified by imaging modalities that miss the target nerve or cannot reliably detect intravascular uptake. 11 The findings of this meta-analysis suggest that US-guided MBB could further impede the ability to accurately identify patients for radiofrequency denervation. However, use of US may be indicated in austere environments or select clinical scenarios where avoiding radiation exposure is a key outcome.…”
Section: Discussionmentioning
confidence: 94%
“…5 For diagnostic criteria, research and review articles abound on the ideal cut-off for designating a block as positive, and the optimal number of blocks that should be performed before lumbar facet radiofrequency ablation (RFA) treatment, with no consensus emerging. [6][7][8][9][10][11] Lumbar facet interventions comprise the second most common procedure performed in interventional pain practices, with millions per year being performed in the USA alone. 12 For lumbar RFA, a recent review of the Marketscan commercial claims and encounters databases from 2007 to 2016 demonstrated a 130.6% overall increase in utilization (9.7% annually).…”
Section: Introductionmentioning
confidence: 99%
“…The rationale for the lumbar facet guidelines to recommend single blocks was based in large part on the incidence of false-negative blocks of the lumbar medial branch nerves, which were estimated to be 47% in a retrospective study by Derby et al [ 299 ] using either 50% (46.7%) or 70% (47.1%) cut-off thresholds. In this study, among the eight patients with initial false-negative blocks who underwent lumbar medial branch RFA after a positive subsequent block, six (75%) experienced a positive outcome.…”
Section: Question 14: How Many Prognostic Blocks Should One Perform Before Rfa?mentioning
confidence: 99%